Integrin Beta 4E Promotes Endothelial Phenotypic Changes and Attenuates Lung Endothelial Cell Inflammatory Responses - Chen, Weiguo; Gard, Jamie M. C.; Epshtein, Yulia; Camp, Sara M.; Garcia, Joe G. N.; Jacobson, Jeffrey R.; Cress, Anne E. (Frontiers in Physiology, 2022)
We previously reported integrin beta 4 (ITGB4) is an important mediator of lung vascular protection by simvastatin, a 3-hydroxy-3-methylglutaryl-coenzyme A-reductase inhibitor. In the current study, we report increased endothelial cell (EC) expression specifically of ITGB4E, an ITGB4 mRNA splice variant, by simvastatin with effects on EC protein expression and inflammatory responses. In initial experiments, human pulmonary artery EC were treated with simvastatin (5 µM, 24 h) prior to immunoprecipitation of integrin alpha 6 (ITGA6), which associates with ITGB4, and Western blotting for full-length ITGB4 and ITGB4E, uniquely characterized by a truncated 114 amino acid cytoplasmic domain. These experiments confirmed a significant increase in both full length ITGB4 and ITGB4E. To investigate the effects of increased ITGB4E expression alone, EC were transfected with ITGB4E or control vector and cells were seeded in wells containing matrigel to assess effects on angiogenesis or used for scratch assay to assess migration. Decreased angiogenesis and migration was observed in ITGB4E transfected EC compared to controls. In separate experiments, PCR and Western blots from transfected cells demonstrated significant changes in EC protein expression associated with increased ITGB4E, including marked decreases in PECAM-1 and VE-cadherin as well as increased expression of E-cadherin and N-cadherin along with increased expression of slug and snail, transcription factors that promote endothelial-to-mesenchymal transition (EndMT). We then investigated the functional effects of ITGB4E overexpression on EC inflammatory responses and observed a significant attenuation of LPS-induced MAPK activation (p-Erk, p-JNK) as well as reduced inflammatory cytokines (IL-6, IL-8) expressed in the media of EC after either LPS or excessive cyclic stretch. Finally, EC expressing increased ITGB4E demonstrated decreased barrier disruption induced by thrombin as measured by transendothelial electrical resistance. Our data support distinct EC phenotypic changes induced by ITGB4E that are also associated with an attenuation of cellular inflammatory responses. These findings implicate ITGB4E upregulation as an important mediator of lung EC protection by statins and may lead to novel therapeutic strategies for patients with or at risk for acute lung injury (ALI).